LEADERSHIP STYLE AND JOB MOTIVATION AMONG HEALTH PERSONNEL IN HOSPITAL SETTING: A SCOPING REVIEW - Saifudin, I Made Moh. Yanuar; Zamani, Ahmad; Yuliyanto, Dwi Joko; Mubarok, Ahmad Sauqi; Rokhmatun, Puji Nur (Universitas Muhammadiyah Ponorogo, 2024)
A scoping review was conducted as part of an investigation. To find publications that were published between 2012 and 2022, the databases PubMed and Scopus were systematically searched. A Preferred Reporting Item for Systematic Reviews and Meta-analyses extension for scoping review (PRISMA-ScR) flow diagram was used in the thorough scoping review to show the whole findings of the search as well as the procedure of including studies in the review. A risk of bias assessment was not done in this study specifically. After collecting 259 articles at first, we screened the full texts and found 6 that met our criteria. Based on the results, six articles were included, and three major themes were identified. The effective leadership style can be classified into three categories. The transformational, transactional, and complex leadership styles are all described in this scoping review as being beneficial in hospital settings. However, to choose the most productive style of leadership for enhancing the performances of healthcare workers and ensuring that guidelines are adhered to, one must use a methodical approach. A scoping review protocol was registered at Open Science Framework (https://osf.io/cju4h) on December 18, 2022